عوامل الخطورة في حدوث الفزر الحملية - بدور, رولا; السيد, فاخر; حمدو, سميحة (Latakia University Journal -Medical Sciences Series, 2018)
هدف الدراسة: دراسة تأثير العوامل الآتية على حدوث الفزر الحملية: وزن الأم, عمر الأم, معدل كسب الوزن خلال الحمل, القصة العائلية, وجود خطوط التمدد ووزن الجنين. طرق البحث ومواده: أجريت الدراسة على الحوامل بعد الأسبوع 24 حملي والنساء بعد الولادة اللواتي ظهرت لديهن الفزر خلال الحمل أو لم تظهر,من مراجعات قسم الأمراض الجلدية في مشفى تشرين الجامعي بين عامي 2016-2017 ممن تحققت فيهن الشروط المطلوبة للدخول في الدراسة (حالة–شاهد).معايير الاستبعاد:النساء اللواتي لديهن فزر على البطن لم تظهر خلال الحمل أو التي ظهرت نتيجة استخدام أدوية ستروئيدية. نظمت استمارة لكل من المشاركات في الدراسة. النتائج: عمر الأم الصغير يترافق مع فزر حملية شديدة. وزن الأم (>60 كغ) ومعدل كسب وزن خلال الحمل(>12كغ)له دور في حدوث الفزر الحملية(p=0,02)(p=0,01). وجدنا علاقة بين تناول مانعات الحمل الفموية قبل الحمل وحدوث الفزر الحملية(p=0,04) القصة العائلية الايجابية لها دور هام بحدوث الفزر(p=0,0001). وضحنا دور وزن الجنين (أكثر من3 كغ) في حدوث الفزر(p=0,001). Objective of the study: The purpose of this study was to identify risk factors associated with striae gravidarum:Maternal age and weight gain during pregnancy, family history and fetal weight. Methods :The study was conducted on pregnant women after 24 weeks of gestation and postpartum women who showed up during pregnancy or not appear of SG from the reviews of the Department of Dermatology at Tishreen Hospital between 2016-2017 in which they met the conditions required to enter the study (case - See.) Exclusion criteria: Women who have a striea not appear during pregnancy or as a result of using steroid medications.A questionnaire was organized for each participant in the study Results: younger maternal age is associated with severe striea. maternal weight (> 60 kg) and the weight gain during pregnancy (> 12 kg) have role in the occurrence of striea(p= 0.02) (p = 0.01) We found a relationship between oral contraceptives prior to pregnancy and striea (p = 0.04) positive family history has an important role in the occurrence of the striea (p= 0.0001) We explained the role of fetal weight( >3 kg) in the occurrence of the striea (p= 0.001)